INTELLECTUAL CAPITAL ON THE PERFORMANCE - Akbar Naslin; Yuki Fitria (Human Resource Management Studies, 2022)
This study aims to prove and analyze the influence of the intellectual capital dimension on the performance of MSMEs in the city of Padang. In this study, 350 MSME entrepreneurs engaged in the culinary field in the city of Padang were used. The analytical method used is multiple regression and t-statistical testing. The data processing is done by using SPSS. Based on the results of testing the first hypothesis, it was found that human capital had no significant effect on the performance of MSMEs in the city of Padang, while structural capital and relational capital had a significant effect on the performance of MSMEs in the city of Padang.